Essai: Is Arctic Palynology a “Blunt Instrument”? - Gajewski, Konrad (Géographie physique et Quaternaire, 2006)
AbstractFor nearly forty years, palynologists and other scientists studying the Quaternary have claimed that palynology, when applied in the Arctic, is a “blunt instrument” for analysing environmental change in this region. In this essay, the author explains why this expression should be laid to rest. Limits to palynological resolution are spatial, temporal and taxonomic. These are discussed and examples are shown where both the temporal and spatial resolution of pollen analyses is far higher than previously thought possible. The supposed “bluntness” of Arctic palynology is due to the way this tool has been applied in Arctic environments rather than inherent limits of palynology in Arctic ecosystems.